Life – Skill Based Learning To Improve Early Child Creativity - Sri Sumiyati; Aini Indriasih; Sumaji Sumaji (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
Early child independency spurs creativity improvement. Essentially, independency is caused by educational effort by implementing life – reliability education since early childhood.This quasi experimental research with pretest and posttest design covered learning scenario arrangement to find out the initial condition of children before intervention. Initially, an assessment in the form of behavioral test was done randomly and was observed. Self – reliability learning promotion assisted by media and the already prepared real activity through various games which were designed by the researcher and teachers. The subjects consisted of B group students taken by total sampling. It was all population taken into sample, consisting of 26 children. The data collection was done by using two collecting instruments: observation and documentation. Before being tested to the respondent, the data was tested to ensure the reliability of the instruments’ functions as well as to check the validity and reliability of the instrument. The data were analyzed statistically by comparative test. The findings showed there was difference of the creativity improvements between pre and post intervention and observation during learning process. There was strong relationship between pre and post training and observation which influenced life – reliability to improve creativity.